Measuring patients' satisfaction toward health tourism in Malaysia through hospital environment, nutritional advice, and perceived value: A study on Chinese exchange students - Li, Liu; Ragavan, Neethiahnanthan Ari; Patwary, Ataul Karim; Baijun, Wu (Frontiers in Public Health, 2022)
Malaysia is a reputed destination for health tourism in the Asia Pacific region for its hospitable nature and good quality of service. Patients' satisfaction has been a key concern in health tourism to maintain the flow of tourists’ arrival for medical purposes. By considering the importance of health tourism and patients’ satisfaction in Malaysia, this study aimed to examine the influence of hospital environment, nutritional advice, perceived value on patients’ satisfaction. This study is cross-sectional in nature and follows a quantitative approach. The researchers used questionnaires as a survey tool to obtain information from the respondents. The sample of this is chosen from Chinese exchange students in Malaysia. Using a systematic random sampling technique, 205 usable responses were selected from the respondents and proceeded with further analysis. The study conducted structural equation modelling using Smart PLS version 3. The results found that hospital environment, nutritional advice, and perceived value significantly influence patients' satisfaction in Malaysia.